The prospects of national scientific and educational field innovative development in the dimension of modern legislation - Головко, Світлана Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Scientific problem of improving regulatory support in the context of the development of innovative research and education in Ukraine is actualized in the article. The author focuses on the fact that in conditions of innovative type of progress the key task of higher education is formation of personality with an innovative type of thinking, who is ready to comprehend and solve problems in a globalized world. In the article it is proved that one of the main factors of transformation of national science and education, its integration into the international innovation space is the developing of a modern regulatory and legal field. It is noted that the new conditions qualitatively change the function of the legislation on education. In particular, in addition to traditional regulatory and security should be considered predictive function, which is the new legal framework encourages innovative development of the industry. The features of the introduction of innovation in the category of regulatory support for research and education sector were showing in the article. It is noted that in Ukraine as a whole formed a relatively independent branch of legislation on education, based on the Constitution of Ukraine and is the law of Ukraine "On Education", "On Higher Education", "On scientific and technical activity" and other legal acts which reflected the problem of innovation. The author detected factors that hinder the achievement of strategic results in innovative research and educational activities and proposed mechanisms to minimize their impact. Proved that one of the main conditions for effective action legislation on education in terms of innovation is to complete the implementation of the Law of Ukraine "On Higher Education" and "On Scientific and Scientific-Technical Activity" as well as a new edition of the "Law on Education", improving other regulatory legal acts exceeded their regulatory capacity.